Heart of a shepherd [compact disc, unabridged] - Parry, Rosanne (Random House/Listening Library, 2009)
Ignatius "Brother" Alderman, nearly twelve, promises to help his grandparents keep the family's Oregon ranch the same while his brothers are away and his father is deployed to Iraq, but as he comes to accept the inevitability of change, he also sees the man he is meant to be.